Correlation of Soil Contamination and Incident of STH Infection in Sukokerto Village Sukowono District Jember Regency - Hermansyah, Bagus; Armiyanti, Yunita; Utami, Wiwien Sugih; Rahmi, Aulya; Aziz, Ayu Munawaroh (Universitas Muhammadiyah Surabaya, 2024)
The most common worm infections are those caused by soil-transmitted helminths (STH) infection. Soil contamination is one of the causes of helminth transmission to humans. Poor environmental sanitation and personal hygiene facilitate the spread and transmission of STH. Jember is a district where the majority of the population lives in rural areas with poor sanitation access. This study aims to determine the correlation between soil contamination and incident of STH infection in Sukokerto Village, Sukowono District, Jember Regency. This cross-sectional analytic observational study was conducted from August 2022 to February 2023. The total of samples in this study was 44 fecal and soil around the house. The data obtained from the laboratory examination showed that the total fecal positive of STH was 11 or 25%, and soil was 13 or 29.5%. The results of the Chi-Square test analysis obtained Ï<0.05 (Ï=0.036, OR=4,457). The results showed a significant relationship between soil contamination and the incidence of STH infection in Sukokerto Village, Sukowo District, Jember Regency